Leitura e escrita como ato responsável: uma experiência de ensino/aprendizagem à luz da filosofia da linguagem do Círculo de Bakhtin - Sant Anna, Telma Gomes Novato (2018)
The present PhD research aims to investigate the reading of literary texts and the writing of texts as an active-responsive understanding of the texts read in the daily school life. The work was developed in a narrative and autobiographical approach, based on the theoretical contributions of the Bakhtin studies. In the professional narrative of the researcher the forms of seeing and conceiving the language during its 32 years of teaching are evident. The conceptions of language defined the way of being a student and teacher of Portuguese Language. By going through the three ways of conceiving language: Language is the expression of thought; Language is an instrument of communication and Language is a form or process of interaction and its methodological implications in the teaching / learning of Portuguese language, the researcher brings reflections on the teaching / learning of Portuguese Language in each mode. Only in the last decade, the researcher positions herself consciously when proposing a teaching / learning experience of reading a literary text: Romance genre for students of the ninth grade of Elementary School in a public school of a large municipality in the interior of the state of São Paulo with the intention of bringing a reflection on why work with literary texts in school everyday and what benefits can bring to improve the practice of reading literary texts and written as counterwords in the classroom, anchored in Bakhtinian interactionism. The experiment generated a significant number of documents from which the survey data was collected. These data were analyzed from the narrative methodology based on the Bakhtinian contributions, which places in the center the subject of language, the conditions of production of discourse, the social, the relations of meaning constructed between the interlocutors, dialogia, argumentation, exotopia and the importance of the presence of the textoliterary in the classroom.